How Nostalgia Drives and Derails Living with Wildland Fire in the American West - Ladino, Jennifer; Kobziar, Leda N.; Kredell, Jack; Cohn, Teresa Cavazos (Fire (Basel, Switzerland), 2022)
Representations of fire in the U.S. are often tinged with nostalgia: for unburned landscapes, for less frequent fires, for more predictable fire behavior, or for a simpler, more harmonious relationship between human communities and wildfire. Our perspective piece identifies four prevalent nostalgic figures that recur in popular representations of wildfire: the Giant Sequoia, the Heroic Firefighter engaged in “the Good Fight”, the Lone Frontiersman, and the “Noble Savage”. We assess the affordances and constraints of each of these figures for helping and/or hindering fire management. We consider how some forms of nostalgia position particular humans as heroes and fire as a villain, how others prioritize the communities that come together to face catastrophic fire events, and how some romanticize Indigenous burning practices. Drawing on knowledge from fire science, human geography, and the environmental humanities, we suggest that a more nuanced understanding of nostalgia can be useful for fire management and for finding healthier ways of living with more fire in the future.